In their own voices: a qualitative study of women's risk for intimate partner violence and HIV in South Africa. - Fox, Ashley M; Jackson, Sharon S; Hansen, Nathan B; Gasa, Nolwazi; Crewe, Mary; Sikkema, Kathleen J (Violence against women, 2007)
This study qualitatively examines the intersections of risk for intimate partner violence (IPV) and HIV infection in South Africa. Eighteen women seeking services for relationship violence were asked semistructured questions regarding their abusive experiences and HIV risk. Participants had experienced myriad forms of abuse, which reinforced each other to create a climate that sustained abuse and multiplied HIV risk. Male partners having multiple concurrent sexual relationships, and poor relationship communication compounded female vulnerability to HIV and abuse. A social environment of silence, male power, and economic constraints enabled abuse to continue. "Breaking the silence" and women's empowerment were suggested solutions.
Keywords: Adult; Aggression; Battered Women; Coercion; Cultural Characteristics; Female; HIV Infections; Humans; Interpersonal Relations; Middle Aged; Narration; Questionnaires; Risk Factors; Sexual Partners; Social Environment; Social Perception; South Africa; Spouse Abuse; Women's Health